Social representation of masculine and feminine sports among Saudi adolescents - Alsamih, Munirah (Frontiers in Psychology, 2024)
The authors declare that she has no conflicts of interest and the research has not funded. This study does not contain any studies involving animals. All procedures performed in studies involving human participants were in accordance with the ethical standards of King Saud University (KSU-HE-23-096). Informed consent was obtained from all individual participants included in the study and their parents. This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors.The author would like to thank Miss Raghad Almutairi, Miss Reem Albaidhani, Miss Sharefa Aloud for helping in data collection.